Ki Hajar Dewantara’s Among System and Mobile Seamless Learning in Islamic Religious Education: A Conceptual Study - Amaliyah, Intan Nur Fauziyah; Ubaidillah, Muh. Hafidh; Faizin, Moh.; Hamid, Abdulloh (MA'ALIM: Jurnal Pendidikan Islam, 2026)
The development of digital technology has led to the emergence of the mobile seamless learning (MSL) paradigm, which allows the learning process to take place flexibly and sustainably across space and time. However, the implementation of digital learning in Islamic Religious Education (PAI) still tends to be technically oriented and does not fully support the formation of character and religious experiences of students. This study aims to reconstruct the Among Ki Hajar Dewantara System from the perspective of mobile seamless learning as the foundation of humanist digital pedagogy in PAI learning. The study uses a qualitative approach with a library research type. Data were obtained through documentation and literature searches from books, national and international journals, and previous studies relevant to the Among System, mobile seamless learning, and Islamic education. Data analysis was carried out using content analysis through the stages of reduction, categorization, interpretation, and conceptual synthesis. The results of the study indicate that the integration of the principles of ing ngarso sung tulodo, ing madya mangun karso, tut wuri handayani, and the concept of Tri Pusat Pendidikan with the MSL paradigm is able to build PAI learning that is humanist, contextual, flexible, and oriented towards the internalization of Islamic values. This reconstruction positions digital technology as a means of sustainably shaping students' morals, spirituality, and learning freedom in the era of digital transformation.